Quality of oxytocin and tranexamic acid for the prevention and treatment of postpartum hemorrhage in Kenya, Nigeria, South Africa, and Tanzania. (28th June 2022) - Ammerdorffer, Anne; Rushwan, Sara; Timms, Rebecca; Wright, Philip; Beeson, Leanne; Devall, Adam J.; Mammoliti, Kristie‐Marie; Alwy Al‐beity, Fadhlun M.; Galadanci, Hadiza; Hofmeyr, G. Justus; Singata‐Madliki, Mandisa; Qureshi, Zahida; et al.
Abstract: Objective: To check the quality of oxytocin and tranexamic acid—two recommended products for prevention and treatment of postpartum hemorrhage (PPH)—used in facilities taking part in an implementation research project to improve PPH diagnosis and management. Methods: Between September 2020 and August 2021, oxytocin and tranexamic acid products used in the study facilities in Kenya, Nigeria, South Africa, and Tanzania were collected and transported in cold storage for analysis. Samples were analyzed according to the International (oxytocin) and British Pharmacopeia (tranexamic acid) standards. Results: Of the 17 unique oxytocin products, 33 individual measurements were made. Only six unique products had adequate content and no related substances exceeding the recommended limits. Of 14 tranexamic acid samples, 10 showed adequate content. One product in Kenya and two products in Nigeria from different manufacturers had a high content of related substances, which classified them as substandard. Conclusion: While we were unable to investigate the origin regarding poor manufacturing or poor storage or both, the high number of substandard oxytocin samples is of great concern. Most of the tranexamic acid samples had adequate content but the presence of impurities in multiple products is worrying and requires further study. Synopsis: A significant number of oxytocin samples are substandard. Tranexamic acid quality is generally adequate across different products.